PEMBINAAN NARAPIDANA ANAK SEBAGAI UPAYA MENCEGAH TERJADINYA PENGULANGAN TINDAK PIDANA (Studi Pada LembagaPemasyarakatan Klas IIA Padang) - Ikhsan, Mohamad (Program Magister Ilmu Hukum Universitas Ekasakti, 2018)
Act No. 12/1995 on Corrections mandates that prisons are not only places to serve punishment for criminals, but also places for coaching while also educating prisoners. Child prisoners also need to be given special attention so that they have the ability to adapt and obey the rule of law applicable after serving time in the penitentiary. However, in practice because the pattern of guidance for child prisoners is similar to the pattern of guidance applied by adult inmates and overcapacity, so that the guidance given does not match what is expected, consequently the child returns to the penitentiary for the second time.